Psychological correlates in women with infertility - Prasad, Madhva; Venkatesh, Shreedhar; Kumar, Sampath; Pentakota, Amrutha; Vijaylakshmi, (Nepal Journal of Obstetrics and Gynaecology, 2022)
ABSTRACTAims: To assess the psychological status of infertile women using the Fertility Problem Inventory and to identify any relationship between characteristics of infertility and the psychological problems.Methods: A prospective, quantitative, descriptive, questionnaire- based study with institutional ethics committee clearance was conducted for two months, on women undergoing infertility treatment. Fertility Problem Inventory Questionnaire was applied and stress levels analyzed. Data were tabulated into Microsoft Excel and statistical analysis was performed in terms of percentages and students t tests for categorical variables.Results: Thirty-two patients were studied in the time period with an average of 30.15 years. Seventy-five percent of the patients were found to be suffering from a moderately severe level of infertility-related stress. The remaining were suffering from a moderate level of infertility-related stress. The duration of marriage was found to have a significant correlation with the stress.Conclusions: Majority (two-thirds) of the study group were suffering from a serious psychological morbidity. Psychological evaluation of people seeking infertility treatment could be considered